Penyimpanan Biogas Menggunakan Karbon Aktif Sekam Padi Dengan Variasi Ukuran Mesh Karbon Aktif - Sentana Putra, I Gede; Ketut Putra Negara, Dewa Ngakan; Sucipta, Made (Teknik Desain Mekanika; Vol 10 No 3 (2022): Juli 2022 : Teknik Desain Mekanika, 2022)
Abstract Simantri is a program of the Provincial Government of Bali which is technically oriented in the fields of agriculture and animal husbandry. Cow dung from simantri can be used as biogas as fuel to turn on the stove. The use of biogas for the wider community has not been optimal due to the limited distribution of biogas. This study is expected to determine the potential of using rice husk waste to become an adsorbent as a biogas storage medium using the ANG (Adsorbtion Natural Gas) system. The method used is the adsorption of biogas at a storage pressure of 100 psi with 70 grams of rice husk activated carbon as the adsorbent, the activated carbon was varied with a mesh size of 70-100, 100-200, and 200-500 at an activation temperature of 325oC. The results of the research in biogas storage showed that the highest mass absorption occurred in the variation of mesh 70-100 and mesh 200-500. Then for testing the biogas content, the highest levels of methane and the lowest carbon dioxide occurred at a mesh variation of 200-500. Keywords: rice bran, biogas, ANG, Carbon Active